Zihar dalam Tafsir Fi Zhilal Al-Qur’an dan Tafsir Al-Mishbah - Arif Munandar; Muslim Djuned (TAFSE: Journal of Qur'anic Studies, 2018)
Zihar is a greeting from a husband to his wife who resembles his wife's back with her mother's back. Saying zihar during the period of ignorance is used by husbands who intend to forbid having intercourse with their wives so that the result is that the wife becomes unlawful for the husband forever. Islam stipulates that it is forbidden to say zihar. However, Allah (swt) gave relief to the people and set kafarat in it as education so as not to repeat these words and attitudes. The problem of zihar arises when a woman makes a complaint to the Prophet about her husband. Then the verse in QS. al-Mujadilah regarding Aus bin Shamit when he visited his wife Khaulah bint Tsa'labah. This paper aims to reveal the thoughts of Sayyid Qutb in Tafsir Fi Zhilal al-Qur'an and M. Quraish Shihab in Tafsir al-Mishbah regarding the issue of zihar. The author uses library research using the maudhu'i and comparative methods. Sayyid Qutb in his commentary concludes that zihar is a husband's saying to his wife that resembles the wife's back with the husband's mother's back, so it must be forbidden like a mother. Meanwhile, Quraish Shihab argues that zihar is a word of a mukallaf to a woman who is lawful to have intercourse with (wife) that the woman is the same as someone who is forbidden to have intercourse, either because of blood relations, marriage, breastfeeding, or for other reasons. Zihar adalah ucapan suami kepada istri yang menyerupakan punggung istri dengan punggung ibunya. Ucapan zihar pada masa jahiliah digunakan oleh suami yang bermaksud mengharamkan untuk menyetubuhi istri sehingga berakibat istri menjadi haram bagi suami untuk selamanya. Islam menetapkan haram hukumnya ucapan zihar. Namun, Allah Swt memberi keringanan bagi umat dan menetapkan kafarat di dalamnya sebagai pendidikan agar tidak mengulang perkataan dan sikap tersebut. Permasalahan zihar muncul ketika seorang perempuan membuat pengaduan kepada Rasul Saw mengenai suaminya. Lalu turun ayat dalam QS. al-Mujadilah berkenaan dengan Aus bin Shamit ketika menzihar istrinya Khaulah binti Tsa’labah. Tulisan ini bertujuan untuk mengungkap pemikiran Sayyid Quthb dalam Tafsir Fi Zhilal al-Qur’an dan M. Quraish Shihab dalam Tafsir al-Mishbah yang berkenaan dengan permasalahan zihar. Penulis menggunakan penelitian kepustakaan dengan menggunakan metode maudhu’i dan komparatif. Sayyid Quthb dalam kitab tafsirnya menyimpulkan bahwa zihar adalah ucapan suami kepada istri yang menyerupakan punggung istri dengan punggung ibu suami, sehingga ia mesti diharamkan seperti ibu. Sedangkan Quraish Shihab berpendapat bahwa zihar adalah ucapan seorang mukallaf kepada wanita yang halal digaulinya (istri) bahwa wanita tersebut sama dengan salah seorang yang haram digauli, baik karena hubungan darah, perkawinan, penyusuan, maupun oleh sebab lain.